IN REFERENCE TO PHONATION LARYNX FIXATION: COMPUTER GRAPHIC RECORD - Sochorova, Hana; Pesak, Josef; Laichman, Stanislav; Grepl, Michal (Biomedical papers, 2003)
The vocal apparatus serves phonation. It represents a biocybernetic self-regulating system, disposing of a feedback network of the central nervous system. The larynx is a self-induced vibrating system. The larynx, functioning as the phonation apparatus of the vocal apparatus, is a source of human voice. In every individual its frequency range corresponds to about eight semitones in speech and about two octaves of the so-called chest register in singing, denoted also as a thoracic or modal voice. This is followed by one more octave of the so-called cranial register or falsetto voice. We were interested in changes of the larynx positions at intonation in the fundamental singing registers, both modal and falsetto, in professional male singers. At our disposal were 11 professional male singers. We investigated changes in the position of the laryngeal structures simultaneously with the aid of an X-ray apparatus, the acoustic and mechanical signals registered by means of the B & K 4369 acceleration recorder. It has been found that at phonation with the modal voice a change in the position of the laryngeal structures takes place in two different ways, whereas the larynx movements at falsetto remain the same. It has been suggested that a complex fixation apparatus participates in the phonation larynx movements. Of the same complex character are also the problems connected with the examination of the entire vocal apparatus. For the purpose of compiling the present pieces of knowledge in the field of human voice studies, we have made the most advantageous use of the presently most complex system Authorware for the production of some interactive multimedial programmes on personal computers.
Keywords: Vocal apparatus / Larynx / Modal voice / Falsetto voice / Phonation larynx fixation